PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR SATUAN POLISI PAMONG PRAJA (SATPOL PP) PROVINSI MALUKU - Visi Wantri Gea; Olivia Laura Sahertian; Join Rachel Luturmas (P3M Politeknik Negeri Ambon, 2026)
This study aims to determine how work discipline affects employee performance at Satpol PP of Maluku Province. This research is based on the importance of discipline as a key factor in improving work effectiveness, since good discipline creates order, responsibility, and compliance with regulations, which in turn impacts employee performance. The research method used is a quantitative method with an associative approach. The population of this study consists of all employees of the Satpol PP of Maluku Province, with the sampling technique carried out using purposive sampling. The research instrument is a questionnaire, while the data analysis technique applies simple linear regression analysis with the help of SPSS software.The results of this study indicate that work discipline has a positive and significant effect on employee performance atSatpol PP of Maluku Province. The higher the level of discipline possessed by employees, the better their performance will be. Work discipline contributes 69.5% to the improvement of employee performance, thus it can be concluded that discipline is an important factor in enhancing work effectiveness. Keywords: Work Discipline, Performance.